ISBAT Nikah Melegalkan Pernikahan Sirri Menurut Hukum Positif Dan Hukum Agama (Studi Di Pengadilan Agama Palangka Raya) - Sanawiah Sanawiah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The purpose of this study was to find out what sirri marriage laws according to Islamic Law and Positive Law, to find harmony and marriage requirements and to find out how the role of Religious Court of Palangka Raya in socialization confirmation marriage. The method used in this research is the method of legal normative. As for the type of research used in this study is inventory regulations that related to confirmation of marriage legalized marriage sirri according to Positive Law and Religious Law. Law wedding sirri results according to Islamic Law and Positive Law, sirri marriage according to Islamic Law illegitimate because it does not have a guardian of marriage, while marriage sirri in the view of the majority of Indonesian society is marriage not recorded but the terms and illegitimate pillars have been met in accordance with Islamic Law. Meanwhile, according to the law of the wedding positive sirri is as where according to Marriage Law in Indonesia if a legal marriage in syar'i then legitimate also according to law